Numerical Study Of The Influence Of Air Flow Through Rectangular Elbow 90 ° With Triangle Inlet Body Disturbance - Aulia, Nur Fatowil; Faradis, Luke Ezra; Su”™udy, Ahmad Hamim; Safarudin, Yanuar Mahfudz; Mulyono, Mulyono; Hermawan, Baktiyar Mei; Sutanto, Bayu (Eksergi, 2024)
AbstrakThis research is to determine the effect of air flow flowing through a 90 ° square elbow with the additional shape of a triangle inlet disturbance body. Simulations were carried out using the Computational Fluid Dynamics (CFD) method to analyze air flow characteristics and changes in flow patterns due to the presence of additional triangular shapes in the flow channel. Numerical simulations are carried out by taking the 90 ° square elbow geometry as the basic model and adding an additional triangle inlet disturbance body shape to it. The simulation results show that the triangle inlet disturbance body significantly influences the air flow inside the elbow. This effect can increase turbulence producing different pressure and velocity contours along the elbow. The effect of flow velocity on the flow in the elbow results in a higher velocity if the form of disturbance is also greater. This research could provide greater understanding of the influence of additional components on fluid flow in channels with similar geometries, opening up potential applications across a wide range of industries.Keywords”” Air flow simulation, Triangle Disturbance, Pressure, Speed